Research note: The critical role of the interaction between Eimeria tenella invasion protein RON2 and host receptor annexin A2 in mediating parasite invasion - Junli Ni; Xiangjie Chen; Yunyun Sun; Yibin Zhu; Haiming Cai; Yongle Song; Minna Lv; Juan Li; Shenquan Liao; Nanshan Qi; Mingfei Sun; Jianfei Zhang; et al. (Poultry Science)
Avian coccidiosis, caused by protozoan parasites of the genus Eimeria, is a globally prevalent and highly pathogenic disease that poses a serious threat to the poultry industry, resulting in significant economic losses. However, the mechanism by which Eimeria species invade host cells remains unclear. Previous studies have identified rhoptry neck protein 2 (RON2) from Eimeria tenella as a critical factor in host cell invasion, but a comprehensive understanding of the role of EtRON2 in host cell invasion and its relationship with E. tenella invasion is lacking. To address this gap, this study focused on the secreted protein EtRON2 from E. tenella and its interaction with host cell receptors. The receptor interacting with the EtRON2 protein was identified through a GST pull-down assay, followed by mass spectrometry, and the interaction was further validated through subcellular co-localization analysis. Furthermore, sporozoites and host cells were treated with a specific antibody targeting the EtRON2/annexin A2 interaction, and the invasion rate of E. tenella was assessed using RT-qPCR to analyze the effect of inhibiting this interaction on host cell invasion by E. tenella. Annexin A2 protein, located on the surface of the host cell membrane, was screened, and the results of the sporozoite invasion assay revealed that inhibiting the interaction between these two proteins reduced F-actin aggregation. Understanding the interaction between the EtRON2 protein and its receptor during parasite invasion could help elucidate the function of the EtRON2 receptor and provide a theoretical foundation for further studies on the invasion mechanisms of E. tenella and the prevention and control of avian coccidiosis.